Preventing Child Marriage through Local Regulation in Bangkalan from a Socio-Legal and Maqāṣid al-Sharīʿah Perspective - Qomaro, Galuh Widitya; Adiyono, Adiyono; Mahaseth, Harsh; Arofik, Slamet (El-Usrah: Jurnal Hukum Keluarga, 2026)
This research has shown that the main institutional problem with child marriage prevention in Bangkalan is not the lack of legal norms, but the lack of the capacity of legal frameworks at the grassroots level. The lack of strong enforcement, the indecisiveness of village officials, and poor coordination between religious courts, KUA officials, and child protection institutions are the problems that can undermine the effective application of the Bangkalan Regent Regulation No. 60 of 2024. Although the regulation offers a holistic system whereby preventive strategies and multisectoral coordination are incorporated, its effect in operation is limited by the culture and economic influences that still legitimize early marriage practices. The paper finds institutional fragmentation, low enforcement capacity, and socio-cultural resistance to be some of the critical challenges in policy implementation. Legal structure, legal culture and socio-economic conditions interact to influence the effectiveness of the legal enforcement. The analysis by the Quantitative Strategic Planning Matrix (QSPM) shows that the most strategic priority is reinforcement of legal enforcement and village-level supervision, but its sustainability requires simultaneous community education and economic empowerment. This study will be of significance to the socio-legal discussion since it will indicate that the efficacy of local regulation is conditional upon the correspondence between the aspects of the legal system, as envisioned by Lawrence M. Friedman, and the moral purpose of the Islamic law, stipulated in maqāṣid al-sharīʿah, especially ḥifẓ al-nasl. Bangkalan case empirically demonstrates that the local regulations can serve as effective tools to translate national child protection commitments into context-sensitive governance as long as they are accompanied by institutional capacity, cultural involvement, and policy strategies.